Gene expression changes in cerebellum induced by dietary restriction - van’t Sant, Lisanne J.; Birkisdóttir, María B.; Ozinga, Rutger A.; Gyenis, Ákos; Hoeijmakers, Jan H.J.; Vermeij, Wilbert P.; Jaarsma, Dick (Frontiers in Molecular Neuroscience, 2023)
Background: Dietary restriction (DR) is a well-established universal anti-aging intervention, and is neuroprotective in multiple models of nervous system disease, including models with cerebellar pathology. The beneficial effects of DR are associated with a rearrangement of gene expression that modulate metabolic and cytoprotective pathways. However, the effect of DR on the cerebellar transcriptome remained to be fully defined. Results: Here we analyzed the effect of a classical 30% DR protocol on the transcriptome of cerebellar cortex of young-adult male mice using RNAseq. We found that about 5% of expressed genes were differentially expressed in DR cerebellum, the far majority of whom showing subtle expression changes. A large proportion of down-regulated genes are implicated in signaling pathways, in particular pathways associated with neuronal signaling. DR up regulated pathways in large part were associated with cytoprotection and DNA repair. Analysis of the expression of cell-specific gene sets, indicated a strong enrichment of DR down genes in Purkinje cells, while genes specifically associated with granule cell did not show such a preferential down-regulation. Conclusions: Our data show that DR may have a profound effect on the cerebellar transcriptome inducing a mild shift from physiology towards maintenance and repair, and having cell-type specific effects.